Synergetics and Fractals in Tribology - Janahmadov, Ahad Kh.; Javadov, Maksim Y.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book examines the theoretical and practical aspects of tribological process using synergy, fractal and multifractal methods, and the fractal and multifractal models of self-similar tribosystems developed on their basis. It provides a comprehensive analysis of their effectiveness, and also considers the method of flicker noise spectroscopy with detailed parameterization of surface roughness friction. All models, problems and solutions are taken and tested on the set of real-life examples of oil-gas industry. The book is intended for researchers, graduate students and engineers specialising in the field of tribology, and also for senior students of technical colleges.
Key Features and Operating Conditions of Tribocontacts -- Scientific Foundations of Stochastic Tribomodeling -- Synergetic Model of Fracture and Mechanics of Fatigue Cracks During Friction -- Fractal Kinetics of Fracture -- Multifractal Analysis of Fatigue Failure -- Fractal Analysis of Fatigue Failure of Kinematic Pair (Oil-Gas X-Mas Tree Valve) -- Fractal Fatigue Analysis of Valved Units of Submersible Pumps -- Flicker-Noise Spectroscopy (Fns) of Dynamics Sygnals and Its Application In Wear of Oil-Field Compressor Units (ofcu).
Keywords: System theory; Coatings; Tribology; Corrosion and anti-corrosives.; Machinery; Mathematical physics; Complex Systems; Coatings; Tribology; Corrosion; Machinery and Machine Elements; Theoretical, Mathematical and Computational Physics